Porto-mesenteric venous thrombosis after laparoscopic sleeve gastrectomy: A case report and systematic review of the 104 cases. Issue 3 (May 2018) - Karaman, Kerem; Aziret, Mehmet; Bal, Ali; Öter, Volkan; Ercan, Metin; Bostancı, Erdal Birol
Summary: Introduction: Porto-mesenteric venous thrombosis (PMVT) is a rare but fatal complication after bariatric surgery. However, an increasing number of PMVT complications have been observed in the last years after laparoscopic sleeve gastrectomy (LSG) operations. Case Report: A 35-year-old male was admitted to the emergency clinic in a septic status with a sudden once of abdominal pain and vomiting. The patient underwent laparoscopic sleeve gastrectomy (LSG) 15 days ago. His physical examination revealed diffuse abdominal tenderness. Abdominal computerised tomography showed a thrombus which was elongated from vena mesenterica superior to vena porta. An emergent laparotomy was performed. A 40 cm of ischemic small bowel segment which began at the 60th cm of Treitz ligament was resected. The gastrointestinal continuity was provided by an end-to-end anastomosis. Patient's postoperative course was uneventful. He was discharged on the 7th postoperative day and was medicated on oral anticoagulation (Warfarin 5 mg/day) for six months. Results: A total of 104 morbidly obese patients who developed PMVT after bariatric surgery are reported in the English literature between 2004 and April 2017. Most of the patients were female (63 cases, 60.5%). The median age was 42.5 years (14–68) and the median body mass index (BMI) was 44 kg/m 2 (31.8–74.6). The most common cause of coagulopathy disorders was protein C and/or S deficiency (9.6%) followed by prothrombin gene mutation (6.7%). LSG was performed in 83 patients (78.8%) and the median intraoperative pressure was 15 mmHg (14–20). The median operation time was 70 min (min–max: 37–192). Fifty-five patients (52.8%) underwent preoperative oral anticoagulant prophylaxis. The median time for PMVT development was 14 days (min–max: 1–453). Of the 104 patients with PMVT, 75 cases (72.1%) underwent postoperative anticoagulant agents such as low-molecular weight heparin (LMWH), heparin drip or infusion, streptokinase or warfarin, whereas the remaining did not receive prophylactic medication. Conclusion: PMVT after sleeve gastrectomy is a rare but fatal complication. Therefore, anti-coagulation prophylaxis with LMWH should be considered at least one month postoperatively.